1981
DOI: 10.1111/j.1365-2559.1981.tb01801.x
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoma of the oesophagus with spindle cell features

Abstract: There is considerable confusion surrounding the histogenesis and nomenclature of squamous cell carcinomas of the oesophagus with spindle cell elements. These tumours, many of which are polypoid, have been variously called carcinosarcoma, pseudosarcoma and polypoid carcinoma of the oesophagus. A study of three recent cases strongly supports the theory that these tumours are squamous cell carcinomas with spindle cell metaplasia. They are not necessarily polypoid and adenocarcinomatous elements may also be presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

1983
1983
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…Other authors, such as Takubo et al [20], Du Boulay and Isaacson [30], and Itabashi et al [42] supported this hypothesis.…”
Section: Discussionmentioning
confidence: 85%
“…Other authors, such as Takubo et al [20], Du Boulay and Isaacson [30], and Itabashi et al [42] supported this hypothesis.…”
Section: Discussionmentioning
confidence: 85%
“…10 Indeed, it has been suggested that by preventing fixation to the host tissue, failure to induce a desmoplastic stromal reaction by sarcomatous cells may play a role in the development of polypoid configuration. 15 Despite the rapid growth of carcinosarcoma, many papers refer to a good prognosis; however, according to Iyomasa et al, 6 the prognosis is not as favorable as previously believed due to the high possibility of hematogenous metastasis in the late period. They emphasized that radical resection with lymph node dissection was necessary to treat carcinosarcomas regardless of the depth of invasion.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of nodal metastasis increases with the depth of invasion and rises dramatically once tumours have penetrated the submucosa. Occasionally an adenocarcinomatous [154], adenocystic [155], neuro-endocrine or glandular component may be present [156]. Skip metastases may be present in oesophageal cancers and distant metastases to the lungs and liver have been reported in up to 50% of all squamous cell carcinomas [141].…”
Section: Deep Oesophageal Cancermentioning
confidence: 99%